A Cross Cultural Comparison of the Contents of Codes of Ethics: USA, Canada and Australia - Wood, Greg (Journal of business ethics, 2000)
This paper examines the contents of the codes of ethics of 83 of the top 500 companies operating in the private sector in Australia in an attempt to discover whether there are national characteristics that differentiate the codes used by companies operating in Australia from codes used by companies operating in the American and Canadian systems. The studies that were used as a comparison were Mathews (1987) for the United States of America and Lefebvre and Singh (1992) for Canada. The major conclusion is that, whilst Australian codes do have some characteristics that differentiate them from the other two groups, it appears that companies in all three cultures are driven by the same motives to develop codes.